Prevalencia de amebas en miel de abeja en los cantones de Guaranda, Chimbo, San Miguel y Chillanes de la provincia Bolivar - Garcia Carrasco, Marco Vinicio (2022)
In the investigation carried out "Prevalence of amoebas in honey bee in the cantons of Guaranda, Chimbo, San Miguel and Chillanes of the Bolívar province" the following objectives were raised; identify the parasite load in bees; establish the parasite load in honey bee; to evaluate the prevalence of amoebas in honey during days 0, 12 and 24. In the methodological framework, the experimental material was 60 dissected bees, 71 honey samples; which were analyzed by the method of microscopic analysis in the research laboratory of the State University of Bolívar. The main results obtained were what; the parasite load in bees occurred in the cantons of Chimbo with 7% and Chillanes with 33%, they are manageable and can be controlled; while in Guaranda and San Miguel there was no parasitism. Regarding the parasite load in honey, it was determined that in the research area there is no presence of amoebas in honey with 100% negative samples; the same ones that were analyzed on days 0, 12 and 24 respectively. With these samples, the health status of the hives was also determined, by determining the existing population where most of the hives were found to be in good condition; its physical characteristics such as coloration and consistency, which was influenced by the life zone where the apiaries and existing bee flora are located.